High invasiveness of pneumococcal serotypes included in the new generation of conjugate vaccines. (8th November 2013) - del Amo, E.; Brotons, P.; Monsonis, M.; Triviño, M.; Iñigo, M.; Selva, L.; Sa‐Leão, R.; Muñoz‐Almagro, C.; Mainardi, J‐L.
Abstract The implementation of the seven‐valent pneumococcal conjugate vaccine, PCV7, has resulted in significant changes in the pneumococcal population being carried and causing disease. We aimed to determine the invasive disease potential of serotypes causing invasive paediatric disease in the era of conjugate vaccines in Catalonia, Spain, and their potential coverage by the 13‐valent pneumococcal conjugate vaccine, PCV13. As a secondary objective, we evaluated whether implementation of PCV7 had resulted in significant changes in the invasive disease potential of the most frequent serotypes circulating in the area. Two pneumococcal collections obtained from children admitted to the University Hospital Sant Joan de Déu (Barcelona, Spain) between 2007 and 2011 were compared: a first set of 159 invasive disease isolates, and a second set of 209 nasopharyngeal isolates recovered from healthy children admitted for minor surgery. The most common invasive serotypes were 1 (24.5%, n = 39), 19A (21.2%, n = 34), 5 (8.8%, n = 14), 7F (8.8%, n = 14) and 3 (5%, n = 8). The most common serotypes in carriage were 19A (10%, n = 21), 6C (9%, n = 19), 23B (8.1%, n = 17), 6A (7.6%, n = 16) and 19F (6.2%, n = 13). A significantly higher propensity to cause invasive disease was observed for serotypes 1, 3, 5, 7F and 19A, all of which are included in PCV13. After false‐discovery‐rate correction, the results were robust for serotypes 1, 5, 7F and 19A. Non‐PCV13 serotypes had a low invasive disease potential. Our data reinforce the need for continuous surveillance and should encourage efforts to introduce universal vaccination with PCV13 in children in our region.